Asymmetric impacts of natural resources on ecological footprints: Exploring the role of economic growth, FDI and renewable energy in G-11 countries. (December 2022) - Sun, Yunpeng; Guan, Weimin; Mehmood, Usman; Yang, Xiaodong
Abstract: Environmental sustainability has become an important agenda for all economies globally. After the Paris agreement and COP26, the world is determined to lower its ecological footprints. In this context, this study investigates the impacts of natural resources, renewable energy, and foreign direct investment (FDI) on ecological footprints (EF). Using a non-linear autoregressive distributed lag approach, we integrate the asymmetric effects of natural resources while addressing cross-section dependence and slope heterogeneity. The findings show that positive shocks in natural resources increase EF by 0.120% compared to negative shocks, reducing EF by 0.072%. These results endorse the asymmetric impact of natural resources. Renewable energy possesses significant negative effects, while economic growth reports positive effects on EF. Moreover, the results validate the FDI hallo hypothesis in the long run. The short-run results report a similar direction of relationship; however, coefficient significance and magnitude vary. Lastly, the error correction term is significantly negative, confirming the convergence toward long-run steady-state equilibrium. Highlights: Asymmetric effects of natural resources on ecological footprints (EF) are explored. Positive shocks in natural resources increase EF by 0.120%. Negative shocks in natural resources decrease EF by 0.072%. FDI-induced Pollution Hallo hypothesis is endorsed in G-11 Countries. Economic Growth (Renewable energy) increase (decrease) EF.